Defects Passivation and Performance Enhancement of AlGaN/GaN HEMTs by Supercritical Hydrogen Treatment - J. K. Lian; Y. Q. Chen; C. Liu; X. Y. Zhang (IEEE Journal of the Electron Devices Society)
In this paper, supercritical hydrogen treatment is used to passivate the defects of normally-on type AlGaN/GaN high electron mobility transistors. By comparing the electrical characteristics of devices before and after the experiment, the treated devices have shown larger on-state current, a negative shift of threshold voltage and shorter gate-lag. In addition, the reliability of the devices before and after treatment is tested by applying a DC reverse bias stress to the gate and the result indicates that the treated devices show less degradation after RB stress. At the same time, through the low-frequency noise test, it is further verified that the defect density near the 2DEG channel reduced from $1.25 × 10^{20}~ {cm}^{-3}{eV}^{-1}$ to $8.94 × 10^{18}~ {cm}^{-3}{eV}^{-1}$ . Based on the above results, a physical model is proposed to demonstrate the passivation mechanism. The original passivation layer and AlGaN barrier layer have many dangling bond defects that can capture electrons and cause virtual gate effect. Supercritical hydrogen penetrates into the material substrate and passivates the dangling bonds. The result of this experiment provides a significant reference for the research of improving the reliability of AlGaN/GaN HEMTs.